A comparative evaluation of three different attachment methods for a video laryngoscope in a surgical setting - Kienle, Linus; Schild, Leon R.; Seitz, Andreas M.; Hahn, Viola D.; Greve, Jens; Hoffmann, Thomas K.; Schuler, Patrick; Boehm, Felix (Laryngoscope investigative otolaryngology, 2025)
Introduction The prerequisite for transoral microsurgery of laryngeal lesions is an uninterrupted line of sight to the operative field. Patients with cervical stiffness or anatomical variations that prevent adequate laryngeal exposure are typically unsuitable for this procedure. In such cases, a curved video laryngoscope may facilitate improved access to the larynx. However, conventional suspension laryngoscopy setups are incompatible with standard video laryngoscopes. Objective This study evaluates three attachment methods for integrating a curved video laryngoscope into a surgical setup, focusing on their resistance to external forces. Methods This study assessed three different attachment methods (3D-printed clamp vs. metal bracket vs. articulated stand) for a video laryngoscope in a surgical setup. External forces, both lateral and rotational (torque), were applied and continuously measured until laryngeal visualization was compromised by displacement of the video laryngoscope. Results The metal bracket demonstrated significantly (p < 0.001) higher resistance to lateral forces (median 184.49 N, 95% CI [181.59-189.61 N]) compared to the articulated stand (median 88.16 N, 95% CI [76.73-88.98 N]) and the 3D-printed clamp (median 55.59 N, 95% CI [54.74-57.58 N]). The articulated stand exhibited significantly (p < 0.005) greater torque resistance (median 9.57 N m, 95% CI [5.65-9.87 N m]) compared to the metal bracket (median 1.58 N m, 95% CI [1.57-2.13 N m]) and the 3D-printed clamp (median 2.46 N m, 95% CI [2.24-2.79 N m]). Conclusion Overall, the articulated stand outperformed the other attachment methods, displaying robust resistance to lateral forces and superior rotational stability. Level of Evidence Level 4.
Zuerst veröffentlicht: 2. Juni 2025
Gesehen am 15.09.2025